Efficient proxy re-encryption design and its application in cloud computing - Du, Jiawei (2016)
Proxy Re-Encryption (PRE) Scheme is a cryptography system that allows a third authorized party to read encrypted cipher text. A kind of PRE based on bilinear pairing is used in this project to realize a cloud storage model that has an improved security level to avoid intolerable loss. A location sharing android application and the corresponding server are deployed in this project to realize the PRE scheme. This report is to describe the motivation, algorithm of PRE and implementations of client application and servers. The following are covered in this report. 1. The motivation, demand and development of PRE cryptography system. 2. The background of cryptography and how the PRE scheme is caught. 3. The design and implementation of android application and java servers; Analysis of the final program. 4. Demonstration and conclusion of the scheme.